Pengaruh Latihan Drill Terhadap Kemampuan Servis Backhand Bulutangkis Mahasiswa - Apriliani, Alma; Arifin, Zaenal; Sonjaya, Azhar Ramadhana (Jurnal Kepelatihan Olahraga, 2024)
This research was motivated by the high number of short backhand servis errors made by badminton athletes who took part in activities at the Garut University Student Activity Unit, Physical Education class of 2019. One of the factors identified as the cause of these errors was the athlete's poor foot position when making the shot. . Therefore, improvement is needed through continuous training, one of which is by using drill exercises. The problem formulation for this research is whether there is an effect of drill training on backhand servis ability, with the aim of assessing the impact of drill practice on badminton athletes' backhand servis ability.The concepts and theories used as references include training concepts, training principles, drilling practice concepts, and badminton game concepts. The results of the research show that there is a positive influence of drill training on backhand servis ability. This is proven by an increase in the average value of the backhand serve after participation in drill practice. Statistical analysis produces a calculated t value = -20.716 and t table = -2.160, with -t calculated -t table (-20.716 -2.160). Apart from that, the probability value (P value) 0.05 or 0.000 0.05, so the null hypothesis (Ho) is rejected. This means that there is a significant difference in backhand servis ability before and after drill practice.Recommendations for this research were given to the UNIGA Student Activity Unit (UKM) Manager to improve the management of UKM activities, the Badminton UKM Manager to improve the quality and quantity of training, and to the campus to further improve the guidance of UNIGA UKM as an implementation of the Tri Darma of Higher Education.